Anastasia [videorecording (DVD)] - Bluth, Don; Goldman, Gary; Ryan, Meg; Cusack, John, 1966-; Grammer, Kelsey, 1955-; Azaria, Hank, 1964-; Peters, Bernadette; Dunst, Kirsten, 1982-; Lansbury, Angela, 1925- (20th-century-Fox family features., 2001)
Animated musical tale of Anastasia, a princess of Russia's Romanoff family who survives assassination and finally flees to Austria.